From livelihoods to leisure and back: refugee 'self-reliance' as collective practices in Lebanon, India and Greece. Issue 2 (4th November 2020) - Carpi, Estella; Field, Jessica Anne; Dicker, Sophie Isobel; Rigon, Andrea
Abstract: Over the last two decades, leading humanitarian agencies in the Global North have increasingly promoted a policy of self-reliance, understood as making individual refugees financially independent from aid assistance through livelihood programmes. However, individual economic autonomy offers an incomplete picture of refugee well-being. Based on fieldwork conducted over 2017 in Halba (Lebanon), Delhi (India) and Thessaloniki (Greece), this multi-site study shows that non-camp refugees build on collective strategies at household, social network and community levels in efforts to develop mechanisms of survival and enfranchisement. These strategies include social and leisure activities as well as income-generating activities which are often organised compartmentally in humanitarian programming. We argue that while leisure and social mingling alone cannot ensure economic sustainability, they are fundamental dimensions of self-reliance as seen by refugees and should therefore be systematically included in livelihood programming. "It is on a living tree that the vine grows" (Ghanaian proverb teaching support, growth and interdependence on one another within the community).